Islamic Law as the Authoritative Source in State Administration of Indonesia - Sopyan, Yayan; Yazwardi; Ade Dedi Rohayana; Imam Yahya; Ismail (Hikmatuna : Journal for Integrative Islamic Studies, 2022)
Many academicians regret the removal of seven words in the Jakarta Charter and consider this a political defeat for Muslims. If the words had not been removed, Islamic law would be simple in its implementation in Indonesia. There was a new hope when the Presidential Decree of July 5th, 1959, stated to return to the 1945 Constitution. The Presidential Decree emphasized that the Jakarta Charter was a series of units in the Constitution. In other words, Islamic laws in the state   administration system in Indonesia could be the authoritative source. This means that Islamic law has a chance to contribute to the Indonesian legal system. This qualitative research used a normative approach in which information was gained from several reliable sources, such as books and journals, to explore and figure out any perspectives about the status of Islamic law as the authoritative source in the state administration of Indonesia. This research showed that Islamic law as the authoritative source could contribute to the legal order applied in Indonesia. As a political product, the law relies on the political situation; nevertheless, Muslims cannot maximize their political roles given the hindrances from external and internal factors. Hence, there is a need to build awareness of Muslims, particularly those becoming lawmakers, to be capable of introducing Islamic laws to the public through the objectification of Islamic laws. Substantially, Islamic law is superior in giving justice, benefits, and legal certainty.